Application of telemedicine in fatigue management for patients with multiple sclerosis: A scoping review - Xiaoyan Gong; Xiaoyu Xue; Rong Gao; Shengya Feng; Xinyu Ji; Jie Zheng; Bowen Xue (PLoS ONE, 2025)
Background Fatigue is a prevalent symptom in people with Multiple Sclerosis, but evidence for the effectiveness of telemedicine in treating this symptom remains incomplete. Despite favorable clinical trial results, its integration into practice and systematic evaluation is limited. Objective The purpose of this research project is to carefully assess how well telemedicine works for managing fatigue in MS patients. Methods This scoping review adhered to the Joanna Briggs Institute methodological framework and followed the preferred reporting items for systematic reviews and meta-Analyses extension for ccoping reviews (PRISMA-ScR) guidelines. reporting guidelines. A search covering literature in both English and Chinese up until December 2024 was carried out in the electronic databases of PubMed, Embase, Web of Science, CINAHL, Cochrane Library, China National Knowledge Infrastructure (CNKI), Wan Fang, and VIP database. Studies that assessed telemedicine-based therapies for patients with multiple sclerosis and documented fatigue-related outcomes were eligible. The collected literature was compiled, examined, and pertinent information was extracted by two independent reviewers. Results A total of 26 papers were included, all in English. Applications(n = 11), wearable devices(n = 8), teleconferences(n = 11), online platforms(n = 5), text messaging(n = 1), virtual reality(n = 1), and game consoles(n = 1) are some of the intervention forms of telemedicine. Remote monitoring(100% of studies), remote guidance(54%), and remote rehabilitation(58%) are some of the functional characteristics of telemedicine. Fatigue characteristics and its impact, health-related quality of life, physical activity, mental health, and the feasibility of remote interventions are among the outcome indicators. While 77% of studies reported statistically significant fatigue reduction, effect sizes varied from small to moderate. Conclusion Telemedicine demonstrates potential as a viable alternative to conventional rehabilitation for managing MS-related fatigue, particularly through multimodal interventions enabling personalized and real-time management. However, the heterogeneity in influencing factors and treatment effects warrants validation through large-scale trials. Future research should prioritize multimodal strategies, optimizing sample composition, extending follow-up periods, and integrating standardized assessment tools to enhance intervention precision.